KEKUASAAN DAN KEPEMIMPINAN SEBAGAI PROSES SOSIAL DALAM BERMASYARAKAT - Jeanne Darc N. Manik SH., M.Hum, - (SOSIOLOGI, 2013)
In the system of society are deliberately structured to achieve specific purposes usually associated with the distribution of power and official authority in formal organizations. However, if a society is to be organized and the integrity of public life is maintained, then the power and authority must be shared on a regular basis, so that everyone will be clear where the power and authority within the organization both horizontally and vertically. Power is an important element in peoples lives because of their role to determine the fate of millions of people. Power is always there in the community, both still simple and complex large societies. The existence of power depending on the nature of the relationship between the ruling (leaders) and forced. There is a leader in one particular area, there is also a leader in many aspects of life. There are leaders and there are followers who seek the actually sought his followers. There are official leaders (formal leaders) and there are informal leaders.Kata Kunci : Power, Leadership, and Social Procces